Factors Controlling the Role of Zn and Reactivity of Zn‐bound Cysteines in Proteins: Application to Drug Target Discovery. Issue 1 (16th September 2013) - Lee, Yu‐Ming; Lin, Yeh‐Fon; Lim, Carmay
Abstract Zinc is an element essential to all forms of life. It can play a predominantly catalytic role or a exclusively structural role in proteins. Here, we provide an overview of important structural and catalytic Zn metalloproteins and highlight the key features distinguishing structural Zn sites from catalytic Zn sites. We elucidate why Zn can assume dual roles in proteins and provide ways to distinguish catalytic Zn sites from structural Zn sites and guidelines for targeting these Zn sites in drug target proteins. We also elucidate why the Zn‐bound cysteines in certain structural Zn‐sites are reactive and how they may be distinguished from inert Zn‐bound cysteines.